Strategies for growth and poverty reduction: Has Tanzania's second PRSP influenced implementation? - Dennis Rweyemamu (Danish Institute for International Studies (DIIS), 2009)
Tanzania's current growth and poverty reduction strategies are contained in its second PRSP. This document, and the processes leading to its formulation, has helped to mobilize donor funds. However, the content of the PRSP is largely irrelevant for implementation, and has contributed little to better inter-sectoral linkages and synergies both of which were its main purposes. The immediate reasons for this irrelevancy include a participatory planning process not aligned with the domestic political process and with no budget constraints which led to a shopping list of un-prioritized initiatives; an implementation machinery around the budget process which in practice does not ensure that resources are allocated in line with the document's priorities; and limited understanding and/or acceptance across the spectrum of government institutions and political leadership that the PRSP is the overall strategic guiding document.
Keywords: 330; Entwicklungsstrategie; Wachstumspolitik; Armutspolitik; Tansania